Stratigraphy of the Lungmachi black shales from the Huaying drill core in southwestern China and its palaeogeographic implications - Sun, Zong-Yuan; Fan, Jun-Xuan; Wu, Lei; Chen, Qing; Chen, Zhong-Yang; Li, Chao (Palaeoworld, 2019)
Core samples from the Huaying well, Sichuan Province, have been analyzed for both graptolite biostratigraphy and carbon isotope chemostratigraphy. The result shows a stratigraphic sequence of Lituigraptus convolutus, Stimulograptus sedgwickii and Spirograptus guerichi biozones, and records a strong positive shift of delta C-13(org) at the base of the Stimulograptus sedgwickii Biozone, which coincides with those from Cornwallis Island (Arctic Canada), Arisaig (Nova Scotia, Canada), and the Barrandian area (Bohemia). Two outcrops were also studied in the Huaying region. The Yanwanggou section shows a continuous, but complicated, stratigraphical sequence, from the upper Katian to the lower-middle Rhuddanian, then a sedimentary hiatus of similar to 3.26 Ma, and finally a continuous sequence from the upper Aeronian to the lower Telychian, whereas the Liziya section and the Huaying well exhibit significant hiatus, which lasted from Hirnantian to middle Rhuddanian or early Aeronian times. Therefore, the eastern boundary of the Central Sichuan Oldland during the Ordovician and Silurian transition can be precisely constrained to a narrow area between the Huaying well-Liziya section and the Yanwanggou section, which indicates that the Central Sichuan Oldland was much larger than previously considered. The present data also indicate the existing of a so far unidentified stage of the Kwangsian Orogeny, which resulted in the uplift of some portions of the Yangtze Platform region and the consequent delay of the transgression in those places. The multi-stage hiatus, spanning at least from the upper Katian to middle Aeronian in the study area, resulted from a combined effect of the Hirnantian glacio-eustatic sea-level fall and the regional tectonic activity of the Kwangsian Orogeny. (C) 2019 Elsevier Ireland Ltd Elsevier B.V. and Nanjing Institute of Geology and Palaeontology, CAS. Published by Elsevier B.V. All rights reserved.